P213 CXR follow-up after Community Acquired Pneumonia (CAP): Outcomes of adherence to guidelines. (12th November 2015) - Eaton, P; Curtis, HJ
Abstract : Introduction and objectives: BTS Community Acquired pneumonia (CAP) guidelines require a chest radiograph (CXR) 6 weeks after discharge in high risk patients. This is the hospital team's responsibility. Malignancy is reported in 1.7% of patients. We wanted to assess how this was organised across our trust and the outcomes, aiming to improve organisation of the service. Methods: Patients were identified via retrospective review of local NIV/COPD and critical care ICNARC databases. Xrays and reports were reviewed and eRecords interrogated for appointments, follow-up CXR and outcomes. Results: 102 patients were identified between December 2013 to January 2015, (mean age 69 and 56 female patients). Only 54 patients had the follow up CXR. 16 patients did not need local follow-up for a variety of reasons: co-morbidities; current malignant diagnosis; CXR clear pre-discharge or usual residence outside geographical area. 7 patients did not attend the organised follow up appointment. Ultimately, 25 patients had no follow up plans made. The majority of follow-up CXR were organised by the hospital team (n = 53) compared to discharge correspondence instructions to GP to request a CXR (n = 14). The hospital requested CXR were significantly more likely to be undertaken, with 88% completed versus 57% from requests to GP (p < 0.05 Chi-square). The majority of CXRs showed resolution of changes (n = 38/54), 3 patients had lung or pleural malignancy diagnosed, 2 patients are having on-going nodule follow-up and 1 patient had atypical mycobacterium diagnosed. 10 patients to date have incomplete resolution of their changes. These end-points were after 62 CXRs, 7 Ct scans, 2 bronchoscopies and 1 pleural biopsy. Conclusion: There is room for improvement within our trust to improve this parameter for CAP patients. This would be best fulfilled by automatic request at time of discharge follow CAP. The follow up clearly requires increasing amounts of work and administration. How does the NHS keep up with guideline requirements and clinical outcomes in the ageing population? The finding of 5.5% (3/54) new malignancy shows the importance of follow-up and is higher than published reports.